Risk of intraocular and other extracutaneous involvement in patients with cutaneous juvenile xanthogranuloma. Issue 3 (28th February 2018) - Samuelov, Liat; Kinori, Michael; Chamlin, Sarah L.; Wagner, Annette; Kenner‐Bell, Brandi M.; Paller, Amy S.; Kruse, Lacey L.; Mancini, Anthony J.
Abstract: Background/Objectives: Cutaneous juvenile xanthogranuloma is an uncommon, usually benign disease affecting infants and young children. Ocular and other systemic involvement have been reported, but their incidence is unclear, and the utility of routine screening is not well established. Our aim was to characterize the risk of ocular and systemic complications in children with cutaneous juvenile xanthogranuloma. Methods: In this retrospective study, we reviewed the medical charts of children with cutaneous juvenile xanthogranuloma seen at Ann and Robert H. Lurie Children's Hospital, Chicago, Illinois, between January 2000 and December 2015. A comprehensive literature review was also performed. Results: Of 338 children with cutaneous juvenile xanthogranuloma, 76 (median age 6 months, 51% female) met inclusion criteria. The most frequently involved site was the head and neck region (40%). In 39 patients (51%), there was a single lesion. Multiple lesions (>5) were evident in 20 patients (26%). Most cutaneous juvenile xanthogranulomas were micronodular (77%). None of the patients had ocular involvement. One patient had multiple asymptomatic hepatic nodules on imaging that regressed spontaneously within several months. Literature review of pediatric cutaneous juvenile xanthogranuloma series, including our cohort, revealed that the incidence of ocular manifestations is 0.24% (7/2949) and of systemic manifestations is 0.75% (22/2949). Conclusion: Cutaneous juvenile xanthogranulomas are generally limited to the skin. Because eye involvement is rare, a routine eye examination is of low yield and probably not warranted in children with no ocular or visual symptoms. New recommendations for systemic screening could not be drawn from this study.